2018
DOI: 10.3389/fonc.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Circulating Tumor Cells (CTCs) in Lung Cancer

Abstract: Lung cancer affects over 1. 8 million people worldwide and is the leading cause of cancer related mortality globally. Currently, diagnosis of lung cancer involves a combination of imaging and invasive biopsies to confirm histopathology. Non-invasive diagnostic techniques under investigation include “liquid biopsies” through a simple blood draw to develop predictive and prognostic biomarkers. A better understanding of circulating tumor cell (CTC) dissemination mechanisms offers promising potential for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 159 publications
2
95
0
Order By: Relevance
“…Previous research has shown that CTCs can also cause tumor recurrence and are related to patient prognosis . The ability to obtain more information from CTCs may therefore offer an avenue toward the early detection of cancer, allowing researchers to gain insight into its the aggressive nature of the tumor and offering a means of monitoring therapeutic responses and disease progression in patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that CTCs can also cause tumor recurrence and are related to patient prognosis . The ability to obtain more information from CTCs may therefore offer an avenue toward the early detection of cancer, allowing researchers to gain insight into its the aggressive nature of the tumor and offering a means of monitoring therapeutic responses and disease progression in patients …”
Section: Introductionmentioning
confidence: 99%
“…6,7 The ability to obtain more information from CTCs may therefore offer an avenue toward the early detection of cancer, allowing researchers to gain insight into its the aggressive nature of the tumor and offering a means of monitoring therapeutic responses and disease progression in patients. [8][9][10] In 2004, the CellSearch system was approved by FDA as a means of detecting CTCs in breast cancer, prostate cancer, and colorectal cancer patients given their promise as biomarkers useful for monitoring chemotherapeutic efficacy. [11][12][13] These CellSearch systems relied upon detecting CTCs based on their surface expression of epithelial cell adhesion molecules (EpCAM) and cytokeratins (CK).…”
Section: Introductionmentioning
confidence: 99%
“…CTCs have shown strong potential in the diagnosis of lung cancer, 42 and currently are being actively considered for their prognostic capacity as well. 43 Overall, clinical evidence supports the potential of the CTC count as a predictor of survival in both patients with small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). 12 For patients with SCLC, which is a particularly aggressive lung cancer affecting approximately 15% of patients, CTCs are capable of distinguishing between Circulating Tumor Cells as Biomarkers/Jin et al chemorefractory and chemosensitive SCLC.…”
Section: Ctcs and Lung Cancermentioning
confidence: 95%
“…CTCs have shown strong potential in the diagnosis of lung cancer, and currently are being actively considered for their prognostic capacity as well . Overall, clinical evidence supports the potential of the CTC count as a predictor of survival in both patients with small cell lung cancer (SCLC) and non–small cell lung cancer (NSCLC) .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation